Influence of the Compliance of the Neck Arteries and Veins on the Measurement of Intracranial Volume Change by Phase-Contrast MRI - Tain, Rong-Wen (2009)
PURPOSE: To assess the influence of arterial and venous vascular compliances in the neck region on the measurement of the change in intracranial volume during the cardiac cycle. MATERIALS AND METHODS: Arterial and venous blood flows were imaged by MRI phase contrast at two different locations, one close to the skull base (upper) and one 2-3 cm lower, around C3 level (lower). Maximal intracranial volume change (ICVC) measurements were derived from the momentary differences between the arterial inflow and venous outflow rates at the upper and lower locations separately to assess the influence of the compliances of the vessel segments bounded by the two different imaging locations. Imaging location for the cranio-spinal cerebrospinal fluid flow was a constant variable in this experiment. RESULTS: The systolic ICVC obtained using the lower location was consistently larger than when using the upper location. Comparison between arterial and venous flow dynamics revealed a much larger changes in flow dynamic and lumen areas in the veins compared with the arteries, which explain the large venous influence on the intracranial volume change measurement. CONCLUSION: Arterial inflow and venous outflow should be sampled at a level close to the skull base (C1-C2) to minimize the influence of the compliance of arteries and the collapsibility of veins for a reliable measurement of ICVC.